A comprehensive view of Kara Sea polynya dynamics, sea-ice compactness and export from model and remote sensing data. - Kern, Stefan; Harms, I; Bakan, S; Chen, Y (PANGAEA, 2015)
The Shelf Seas of the Arctic are known for their large sea-ice production. This paper presents a comprehensive view of the Kara Sea sea-ice cover from high-resolution numerical modeling and space-borne microwave radiometry. As given by the latter the average polynya area in the Kara Sea takes a value of 21.2 × 10**3 km**2 ± 9.1 × 10**3 km**2 for winters (Jan.-Apr.) 1996/97 to 2000/01, being as high as 32.0 × 10**3 km**2 in 1999/2000 and below 12 × 10**3 km**2 in 1998/99. Day-to-day variations of the Kara Sea polynya area can be as high as 50 × 10**3 km**2. For the seasons 1996/97 to 2000/01 the modeled cumulative winter ice-volume flux out of the Kara Sea varied between 100 km**3/a and 350 km**3/a. Modeled high (low) ice export coincides with a high (low) average and cumulative polynya area, and with a low (high) sea-ice compactness in the Kara Sea from remote sensing data, and with a high (low) sea-ice drift speed across its northern boundary derived from independent model data for the winters 1996/97 to 2000/01.
(Table 1) Ice flux, polynya area and sea-ice drift speed in the Kara Sea during winter (Jan-Apr) 1997-2001
Keywords: Estimated from monthly averaged daily ECMWF surface wind speed data; Ice flux; KAR; Kara Sea; Percentage; Polynya area; Speed